Engineered cementitious composites for effective strengthening of unreinforced masonry walls - Maalej, M. (2015)
In this paper, a total of 18 masonry wall panels were tested under both quasi-static and dynamic loadings to assess the extent to which a cementitious-based material known as Engineered Cementitious Composite (ECC) can enhance the out-of-plane resistance of unreinforced masonry (URM) walls. The masonry wall panels, which were retrofitted with an ultra-ductile hybrid-fiber ECC, were subjected to three types of load patterns, namely, patch load, uniformly-distributed load and low-velocity projectile impact. The results obtained from the above tests showed that the proposed ECC-strengthening systems are effective in increasing the ultimate load-carrying capacity of URM walls, improving their ductility, enhancing their resistance against multiple low-velocity impacts and preventing sudden and therefore catastrophic failure.